Doppler patterns in growth restricted foetuses: determinants and outcome in a tertiary hospital in South Kerala, India - Shenoy, Heera T.; Shenoy, Sheela; James, Sonia X. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Foetal growth restriction refers to a condition in which the foetus is unable to achieve its genetically determined growth potential. Doppler velocimetry in FGR not only decides the optimum time of delivery but also the optimum mode of delivery and so authors evaluated the Doppler patterns in growth restricted fetuses. Methods: Nested case-control study conducted among normal and abnormal Doppler groups at a tertiary care teaching hospital in the year 2017. Results: Among 82 growth restricted foetuses, 54 of them had normal Doppler patterns (65.85%) and 28 had abnormal Doppler patterns (34.15%).13(46.5%) had umbilical S/D elevation,2 (7.14%) had AEDV,1(3.57%) with REDV and 12 (42.8%) with CPR<1. Mean maternal age was slightly higher in the abnormal Doppler group. FGR babies with abnormal velocity waveforms had shorter diagnosis to delivery interval than those with normal Doppler and decision for delivery was taken at a lower gestational age. (p value-0.001). Mothers of FGR babies with abnormal Doppler studies underwent emergency caesarean section for non-reassuring foetal heart patterns. (p value-0.001) The mean birth weight was higher (2201.80gm) in Doppler normal FGR and it was 1929.46grams in abnormal umbilical Doppler group and 1363.33gm in AREDV (pvalue-0.001). Growth restricted with normal Doppler had shorter NICU stays than with abnormalities (p value-0.003). Term FGR went home early than early preterm. (p value-0.001). Conclusions: Growth restricted foetuses with normal umbilical velocimetry are at a lower risk than those with abnormal velocimetry in terms of prolonged diagnosis-delivery interval and shorter NICU days. The need for neonatal resuscitation at birth was more in babies with abnormal Doppler velocimetry and absent diastole /reversed diastolic flow of umbilical artery velocimetry.